2019
DOI: 10.1002/ajmg.a.61409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurocognitive issues associated with Bosch‐Boonstra‐Schaaf optic atrophy syndrome: A case study

Abstract: Nuclear receptor subfamily 2 group F member 1 (NR2F1) is an orphan receptor and transcriptional regulator that is involved in neurogenesis, visual processing and development, and cortical patterning. Alterations in NR2F1 cause Bosch-Boonstra-Schaaf optic atrophy syndrome (BBSOAS), a recently described autosomal dominant disorder characterized by intellectual and developmental disabilities and optic atrophy. This study describes the clinical and neurocognitive features of an individual with a de novo nonsense v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“… 27 In the current patient cohort, 22 individuals with pathogenic variants in NR2F1 were investigated, including familial cases. Despite the high prevalence of visual system deficits in previously reported individuals with NR2F1 variants, 9 , 14–18 , 28 there are limited data on the ocular phenotype and the disease mechanisms that contribute to visual loss in affected individuals, since previous reports mainly focussed on the systemic clinical features. 19 , 29 Furthermore, the developmental pattern and timing of NR2F1 expression in different human retinal cell types have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In the current patient cohort, 22 individuals with pathogenic variants in NR2F1 were investigated, including familial cases. Despite the high prevalence of visual system deficits in previously reported individuals with NR2F1 variants, 9 , 14–18 , 28 there are limited data on the ocular phenotype and the disease mechanisms that contribute to visual loss in affected individuals, since previous reports mainly focussed on the systemic clinical features. 19 , 29 Furthermore, the developmental pattern and timing of NR2F1 expression in different human retinal cell types have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the difficulty of obtaining high‐resolution magnetic resonance imaging (MRI) at young age, has limited the investigation of possible brain malformations, which could correlate with the high frequency of ID (more than 80%) and epileptic seizures (40%) in BBSOAS patients. New reports are constantly expanding the BBSOAS clinical spectrum (Chen et al , ; Martín‐Hernández et al , ; Bojanek et al , ; Park et al , ; Rech et al , ), as more patients are identified and the pathophysiology of different brain regions or different organs starts to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, в недавно опубликованной работе E. K. Bojanek и соавт. [10] представлено описание больного мужчины с нонсенс-мутацией с.82С>Т (р.Gln28*) в области N-концевого участка гена NR2F1, клиническая картина которого характеризовалась избирательным нарушением невербальных функций при сохранности речи.…”
Section: клинический разборunclassified
“…К настоящему времени описаны 36 мутаций в гене, 24 из которых -однонуклеотидные замены (миссенс / нонсенс-мутации), 11 -делеции различных размеров и 1 -комбинированная хромосомная перестройка с включением локуса гена [1,[4][5][6][7][8]. Обнаружен полиморфизм клинических признаков у больных с различными типами мутаций, нарушающими аминокислотную последовательность отдельных доменов белка, что, по мнению большинства авторов, обусловливает необходимость продолжения исследований, направленных на выявление клинико-генетических корреляций при СББШ [2,9,10]. Результаты таких исследований позволят оптимизировать диагностику заболевания и прогнозировать тяжесть клинических проявлений у больных с различной локализацией и типами мутаций в гене.…”
Section: Introductionunclassified